Needs assessment of mental health training for Auxiliary Nurse Midwives: a cross-sectional survey - Simkhada, Bibha; Sharma, Geeta; Pradhan, Samridhi; van Teijlingen, Edwin; Ireland, Jillian; Simkhada, Padham; Devkota, Bhimsen (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Mental health in pregnant women and new mothers is increasing recognised on the global health agenda. In Nepal mental health is generally a difficult to topic to discuss. THET, a London-based organisation, funded Bournemouth University, and Liverpool John Moores University in the UK and Tribhuvan University in Nepal to train community-based maternity workers on issues around mental health. This paper reports on a quantitative survey with nearly all Auxiliary Nurse Midwives in Nawalparasi (southern part of Nepal). The findings illustrate the lack of training on mental health issues related to pregnancy and childbirth in this group of health workers. Thus the paper’s conclusions stress the need for dedicated training in this field. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.20-26